Students' Perception of Project Based Learning in Microteaching Class - Annisya Amelia Alyani; Ratmanida Ratmanida (Journal of English Language Teaching, 2021)
Project Based Learning as one of the methods proposed by the 2013 curriculum providing many advantages there are also disadvantages which rise to various perceptions. The purpose of this study is to describe students’ perceptions of project based learning in the microteaching class at the English Department, Universitas Negeri Padang. This research used descriptive quantitative research. The sample for this research was 56 microteaching students of English Department in Universitas Negeri Padang. The data collection technique used in this research was a questionnaire with 6 indicators through Google form application. Therefore, the results of this study showed that the majority of microteaching students in English Department had a positive or good perception of the implementation of project based learning. The students agree that the use of project based learning motivates students to learn and be more active in class, improves students’ collaboration and communication skills, and improves their time management skills. However, the students still encounter several obstacles such as students with a weakness in data collection having difficulties in the learning process, some students being less active in group work, and the time allocation. Students’ perceptions of project are influenced by several factors.